2017
DOI: 10.1200/jco.2017.35.15_suppl.9033
|View full text |Cite
|
Sign up to set email alerts
|

A phase 1 study of osimertinib and bevacizumab as initial treatment for patients with EGFR-mutant lung cancers.

Abstract: 9033 Background: EGFR tyrosine kinase inhibitors (TKI) are the recommended first line treatment for EGFR-mutant lung cancers. Osimertinib, an EGFR TKI that inhibits both sensitizing EGFR mutations and EGFR T790M, is approved for use after progression on an EGFR TKI with evidence of EGFR T790M, and is currently being assessed as initial treatment for EGFR-mutant lung cancers. The addition of bevacizumab to erlotinib resulted in improved progression free survival (PFS) compared to erlotinib alone as initial tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…The combination arm demonstrated statistically significant improved PFS and objective response over erlotinib monotherapy, thus supporting the hypothesis of synergism with dual inhibition of EGFR and VEGF pathways. The combination of osimertinib with bevacizumab is being investigated and the first phase I results were reported in 2017, showing that the combination is tolerable (45). Three phase II studies with this drug combination in various lines of treatment are currently ongoing (NCT02803203, NCT03133546, NCT02971501, see Table 2).…”
Section: In Combination With Other Targeted Tkis or Biological Agentsmentioning
confidence: 99%
“…The combination arm demonstrated statistically significant improved PFS and objective response over erlotinib monotherapy, thus supporting the hypothesis of synergism with dual inhibition of EGFR and VEGF pathways. The combination of osimertinib with bevacizumab is being investigated and the first phase I results were reported in 2017, showing that the combination is tolerable (45). Three phase II studies with this drug combination in various lines of treatment are currently ongoing (NCT02803203, NCT03133546, NCT02971501, see Table 2).…”
Section: In Combination With Other Targeted Tkis or Biological Agentsmentioning
confidence: 99%
“…However, the combination with vascular endothelial growth factor inhibition is in early stages of investigation. 21 Another more general combinatorial approach currently in exploration is the use of immunotherapy in combination with EGFR TKIs for patients with EGFR-mutant NSCLC. Although single-agent immunotherapy with programmed cell death protein 1/ programmed death-ligand 1 inhibitors has shown limited in efficacy in patients with EGFR-mutant lung cancers, 22 combining EGFR TKIs with immune checkpoint inhibitors is an approach that currently is being explored in numerous clinical trials.…”
Section: Improving Therapies For Egfr-mutant Nsclc/arbour and Rielymentioning
confidence: 99%
“…Whether we can observe similar improvement in outcomes with newer EGFR TKIs, such as osimertinib, is a yet unanswered question. However, the combination with vascular endothelial growth factor inhibition is in early stages of investigation . Another more general combinatorial approach currently in exploration is the use of immunotherapy in combination with EGFR TKIs for patients with EGFR‐mutant NSCLC.…”
mentioning
confidence: 99%
“…These findings indicate that the PFS of patients with pleural or pericardial effusion is expected to be prolonged with combination use of an EGFR-TKI plus bevacizumab compared with that with an EGFR-TKI alone. However, although phase I clinical trial data have been reported for the combination of osimertinib plus bevacizumab and demonstrated their safety, the efficacy remains unclear, 14 particularly in patients with pleural or pericardial effusion.…”
Section: Introductionmentioning
confidence: 99%